Radioprotective Effects of Folic Acid on Hematological Parameters and Bone Marrow Histology in Male Rabbits Exposed to X-Ray Irradiation - Essam, Haiba; Abdulsayid, Muneerah; Alsunosi, Munay; Srgewa, Amal (AlQalam Journal of Medical and Applied Sciences, 2025)
Ionizing radiation is known to induce significant damage to the hematopoietic system, primarily compromising bone marrow function. Folic acid plays a crucial role as a cofactor in one-carbon metabolism and various cellular processes, including DNA synthesis and repair. This study examines the potential radioprotective effects of folic acid on hematological parameters and bone marrow histology in male rabbits subjected to X-ray irradiation. The experimental design included four groups: (1) Control, (2) Folic acid supplementation, (3) X-ray exposure, and (4) Combined folic acid supplementation and X-ray exposure. Hematological analysis demonstrated a significant decline in white blood cell (WBC), red blood cell (RBC), and platelet (PLT) counts following X-ray exposure, indicating radiation-induced hematopoietic suppression. Notably, folic acid supplementation partially restored these parameters, suggesting its role in promoting hematopoietic recovery. Additionally, histological examination of bone marrow revealed increased cellularity in folic acid-treated groups, further supporting its protective effects against radiation-induced myelosuppression. These findings indicate that folic acid supplementation may attenuate the adverse hematopoietic effects of ionizing radiation, underscoring its potential as a radioprotective agent. تُعرف الأشعة المؤينة بتسببها في أضرار كبيرة للجهاز المكون للدم، مما يؤدي بشكل أساسي إلى ضعف وظيفة نخاع العظم. حمض الفوليك يلعب دورًا حيويًا كعامل مساعد في عمليات التمثيل الأحادي للكربون والعديد من العمليات الخلوية، بما في ذلك تخليق وإصلاح الحمض النووي. تهدف هذه الدراسة إلى فحص التأثيرات الإشعاعية الوقائية المحتملة لحمض الفوليك على المعايير الدموية وتاريخ نخاع العظم المرضي في ذكور الأرانب المعرضة للأشعة السينية. شمل التصميم التجريبي أربع مجموعات: (1) مجموعة التحكم، (2) مجموعة مكملات حمض الفوليك، (3) مجموعة التعرض للأشعة السينية، و(4) مجموعة الجمع بين مكملات حمض الفوليك والتعرض للأشعة السينية. أظهر التحليل الدموي انخفاضًا ملحوظًا في تعداد كريات الدم البيضاء وكريات الدم الحمراء والصفائح الدموية بعد التعرض للأشعة السينية، مما يشير إلى كبت تكون الدم الناجم عن الإشعاع. ومن الجدير بالذكر أن مكملات حمض الفوليك أدت إلى استعادة جزئية لهذه المعايير، مما يشير إلى دوره في تعزيز التعافي الدموي. بالإضافة إلى ذلك، كشف الفحص النسيجي لنخاع العظم عن زيادة في كثافة الخلايا في المجموعات المعالجة بحمض الفوليك، مما يدعم تأثيره الوقائي ضد كبت النخاع الناجم عن الإشعاع. تشير هذه النتائج إلى أن مكملات حمض الفوليك قد تخفف من التأثيرات الدموية الضارة للإشعاع المؤين، مما يبرز إمكانيته كعامل وقائي إشعاعي